Distictive Sport Youtube Channel Assesment Through The Methodological Approach Of Netnography (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The growth of internet and the computers complexities has changed the way humans obtain information and communicate has undergone significant changes. The internet is the backbone of information and communication facilities, while various web-based services on the internet, such as social media, become an enabler for people nowadays in creating, distributing dan obtaining content, including when humans communicate on social media which is a form of content creation. Certain YouTube channels have their own culture, even each channel and each audience that is part of it will form a unique culture. This research will reveal the culture of one of the sports genre channels, the areas reviewed include Computer Mediated Communication and aspects of virtual communities. This study uses the Netnography method, which is a form of ethnography that is adapted for a social world that is mediated by computer devices to expose the culture of distictive sport youtube channel